Jasplakinolide induces primary cilium formation through cell rounding and YAP inactivation. - Tomoaki Nagai; Kensaku Mizuno (PLoS ONE)
Primary cilia are non-motile cilia that serve as cellular antennae for sensing and transducing extracellular signals. In general, primary cilia are generated by cell quiescence signals. Recent studies have shown that manipulations to increase actin assembly suppress quiescence-induced ciliogenesis. To further examine the role of actin dynamics in ciliogenesis, we analyzed the effect of jasplakinolide (Jasp), a potent inducer of actin polymerization, on ciliogenesis. Unexpectedly, Jasp treatment induced ciliogenesis in serum-fed cells cultured at low density. In contrast, Jasp had no apparent effect on ciliogenesis in cells cultured at higher densities. Jasp-induced ciliogenesis was correlated with a change in cell morphology from a flat and adherent shape to a round and weakly adherent one. Jasp treatment also induced the phosphorylation and cytoplasmic localization of the YAP transcriptional co-activator and suppressed cell proliferation in low density-cultured cells. Overexpression of an active form of YAP suppressed Jasp-induced ciliogenesis. These results suggest that Jasp induces ciliogenesis through cell rounding and cytoplasmic localization and inactivation of YAP. Knockdown of LATS1/2 only faintly suppressed Jasp-induced YAP phosphorylation, indicating that LATS1/2 are not primarily responsible for Jasp-induced YAP phosphorylation. Furthermore, overexpression of active Src kinase suppressed Jasp-induced cytoplasmic localization of YAP and ciliogenesis, suggesting that down-regulation of Src activity is involved in Jasp-induced YAP inactivation and ciliogenesis. Our data suggest that actin polymerization does not suppress ciliogenesis per se but rather that cell rounding and reduced cell adhesion are more crucially involved in Jasp-induced ciliogenesis.